Activity-based chemical proteomics reveals caffeic acid ameliorates pentylenetetrazol-induced seizures by covalently targeting aconitate decarboxylase 1 - Guanjun Li; Ling Huang; Di Gu; Peili Wang; Letai Yi; Wenhua Kuang; Ying Zhang; Junzhe Zhang; Dandan Liu; Qiaoli Shi; Huan Tang; Jichao Sun; et al. (Cell Communication and Signaling)
Abstract Background Epilepsy is a neurological disorder characterized by recurrent seizures, tightly associated with neuroinflammation. Activation of inflammatory cells and molecules in damaged nervous tissues plays a pivotal role in epilepsy. Caffeic acid, one of the most abundant polyphenols in coffee, has shown potent protective effects as a phytomedicine in various neurological disorders. However, the direct protein targets and exact molecular mechanisms of caffeic acid in epilepsy, remain largely elusive. Purpose This study aimed to explore the protective effects of caffeic acid in epilepsy and elucidate its underlying mechanism. Methods In this study, we established pentylenetetrazol-induced acute and kindling models of seizures. Additionally, a BV2 microglial cellular inflammation model was established by lipopolysaccharide stimulation. The potential direct protein targets of caffeic acid in BV2 cells were analyzed using an activity-based protein profiling (ABPP) with a caffeic acid probe. Various methods such as pull-down assay, immunofluorescence and cellular heat transfer assays were used for experimental validation. The anti-inflammatory effects of caffeic acid in LPS-activated BV2 cells was proved by knocking down the target protein. Results Here, we found that caffeic acid exhibits antiepileptic effects in pentylenetetrazol-induced epilepsy mice and exerts anti-neuroinflammation effect in vivo and in vitro. Besides, we discovered that caffeic acid directly binds to aconitate decarboxylase 1 and influenced its enzymatic activity. Moreover, we indicated that caffeic acid exhibits anti-neuroinflammation effect through aconitate decarboxylase 1 mediated PERK-NF-κB pathway in vitro. Conclusion In summary, this study elucidates, for the first time, the potential antiepileptic targets and mechanism of action of caffeic acid using the ABPP strategy. Our study provides evidence supporting the utilization of caffeic acid as a promising therapeutic agent for treating epilepsy and neuroinflammation-related disorders.